2022
DOI: 10.1007/s11356-022-23363-4
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the influencing factors and constructing incentive pattern of residents’ waste classification behavior using PCA-logistic regression

Abstract: With the acceleration of urbanization, domestic waste has become one of the most inevitable factors threatening the environment and human health. Waste classification is of great significance and value for improving urban environmental quality and promoting human well-being. Based on the theory of planned behavior, we added external and socio-economic factors to systematically examine how they affect residents’ waste classification behavior (WCB). We collected 661 valid data through a questionnaire survey cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…And then, based on the cumulative contribution of more than 70%, the five principal components were extracted as the principal components for inclusion in the final modeling (Table III). 20,21 Subsequently, we computed the eigenvector coefficients (Zi) and utilized them to establish a linear model for each PC, producing the five variables PC1, PC2, PC3, PC4, and PC5. italicZigoodbreak=loading valueEigenvalue …”
Section: Resultsmentioning
confidence: 99%
“…And then, based on the cumulative contribution of more than 70%, the five principal components were extracted as the principal components for inclusion in the final modeling (Table III). 20,21 Subsequently, we computed the eigenvector coefficients (Zi) and utilized them to establish a linear model for each PC, producing the five variables PC1, PC2, PC3, PC4, and PC5. italicZigoodbreak=loading valueEigenvalue …”
Section: Resultsmentioning
confidence: 99%
“…Due to the existence of the status of unbalanced development between urban and rural areas in China, there are differences in the influencing elements that determine whether urban and rural residents participate in waste sorting. Residents, as the producers of domestic waste, are also the executors of sorting governance, and their behavior affects the effectiveness of waste sorting governance [ 7 ]. A fuller comprehension of the constraints influencing these actions is required to enhance the effectiveness of waste sorting and achieve the coordinated development of urban and rural areas.…”
Section: Introductionmentioning
confidence: 99%
“…According to TPB, behavioral attitudes, subjective norms, and perceived behavioral control, all have an impact on a person's purpose [ 11 ]. Within the TPB's framework, several scholars have investigated the WSB of residents in different regions of China and concluded that subjective norms, attitudes, and perceived behavioral control all promote the generation of residents' intention to sort waste [ 4 , 10 , 12 ], but some scholars believe that subjective norms have a negative influence [ 7 ]. Numerous research has demonstrated the feasibility of the TPB for predicting WSB [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Waste recycling requires waste separation at the source [ 2 ]. Factors such as awareness, education, social norms, perceived benefits, structural barriers, motivation, attitude, subjective norms, self-efficacy, perceived behavioural control, behavioural intentions, normative feedback, and environmental factors have an impact on waste sorting behaviour [ [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] ]. Surveys show that waste separation is very important for the preservation and improvement of the environment [ [20] , [21] , [22] ].…”
Section: Introductionmentioning
confidence: 99%